Jornada 1a Internacional De Ele: a remarkable journey of learning & connections - Azlina, Mohd Ariffin; Siti Ainun Jariyah, Hassan (UMPSA, 2025)
KUALA LUMPUR, 22 February 2025 - Jornada 1a Internacional De Ele (The 1st International of Ele) Seminar was organized by Asociación de profesores y estudiantes de la lengua Española en Malasia in collaboration with the Embassy of Spain, Aula Cervantes, Universidad de Alcalá (Spain) and Universiti Malaya. This prestigious seminar brought together Spanish language teachers, lecturers, and enthusiasts across Malaysia and Spain.